Building medieval worlds : Unreal Engine 5 Modular Kitbash. (Packt Publishing, 2023)
This course offers something for both aspiring game developers and enthusiasts looking to learn Unreal Engine 5. With over 250 modular assets, you can bring to life a medieval fantasy world complete with bustling towns, majestic castles, and intricate canal systems. You will learn unique techniques to create stylized structures, functional water systems with submergible boat assets, and animated native-enabled foliage to enhance the natural side of your world. The course covers a vast array of topics that guide you through every aspect of game development. You will learn to build entire towns and blacksmith shops with ease using the massive modular pack and create custom prop collections using blueprints to make your world come to life. In addition, you will learn to create a fully functional open-world system material with distance-based blending, noise masking, and automatic material transitions. The course also covers creating large-scale cities on the go with Modeling mode, deforming modular assets such as merging bridge pieces and bending bridges using a curved deformed. By the end of the course, you will be able to immerse yourself and your players in a fully functional medieval world of your own creation, whether it's a small village or an entire city. The possibilities are endless with the skills you will gain from this comprehensive course. What You Will Learn Build a medieval castle or city using modular assets Create complex environments with terrain and foliage Implement advanced lighting techniques for day and night scenes Learn how to use blueprints to create interactive elements Understand the basics of game mechanics and design Explore world-building principles and techniques Audience This course is perfect for 3D modelers, game designers, RPG fans, and anyone enthusiastic about Unreal Engine 5. Whether you are a beginner or an experienced designer, this course will teach you how to use a medieval castle kitbash comprising 241 individual pieces to build an entire castle or city. If you are excited about exploring the new and exciting changes in Unreal Engine 5, this course is a must for you. To benefit from the course, all you need is a computer with a downloaded version of Unreal Engine 5, and a thirst for learning 3D modeling, animation, and game engine integration. About The Author 3D Tudor Limited By Neil Ian Bettison: 3D Tudor Limited By Neil Ian Bettison, Neil Bettison is a professional 3D artist with nine years of modelling experience, including assets, characters, and environments. After attending the University for Creative Arts (UCA) for a BA (Hons) Computer Games Arts degree, Neil began freelancing. In 2019, Neil Bettison founded 3D Tudor, a YouTube channel, to help other game developers because of his passion for 3D modeling. Neil's instructor style--his to-the-point instructions and clear guidance--makes him an excellent tutor. Neil uses Blender for particle effects and complex asset animation. Neil can use two popular game engines, Unreal Engine 5, and Unity, with many years of experience in both.